TOP2A Drives Oral Squamous Cell Carcinoma Initiation and Progression Through Activation of the TGF ‐β2/Smad Signaling Pathway - Xueying Zhang; Shaohong Zhang; Chong Chen; Shuhan Zhou; Huiming Yu; Wei Zhang (Journal of Oral Pathology & Medicine, 2026)
ABSTRACT Objective TOP2A has been implicated in the progression of multiple malignancies; however, its clinical significance and biological role in OSCC remain poorly understood. This study aimed to comprehensively investigate the expression, prognostic value, biological functions, and molecular mechanisms of TOP2A in OSCC through an integrative, multilevel approach that combined multi‐cohort bioinformatics analyses, clinical immunohistochemical validation, and both in vitro and in vivo functional experiments. Methods Multi‐cohort bioinformatics analyses were first performed to evaluate TOP2A expression, prognostic relevance, and potential downstream signaling pathways. These findings were further validated using clinical OSCC specimens by IHC and western blot analysis. The biological functions of TOP2A were assessed through a panel of in vitro functional assays and in vivo xenograft models. Mechanistically, the involvement of the TGF‐β2/Smad pathway was examined by integrating transcriptomic profiling with pathway validation and functional rescue experiments using TGF‐β2 overexpression. Results TOP2A is aberrantly overexpressed in OSCC, and it was associated with shortened overall survival in affected individuals. TOP2A silencing impaired cell proliferation, invasion, migration, and promoted apoptosis, whereas in vivo it inhibited tumor growth. In addition, TOP2A can activate the TGF‐β2/Smad pathway and promote the biological behavior of OSCC cells by this pathway. Conclusions These findings suggest that TOP2A is upregulated in OSCC and may promote tumor progression via the TGF‐β2/Smad signaling pathway. Our results support TOP2A as a potential prognostic biomarker and therapeutic target in OSCC.